Effects of organizational culture on organizational effectiveness in Islamic Azad Universities, Northwest of Iran / Mahboub Sheikhalizadeh Heris - Sheikhalizadeh Heris, Mahboub (Faculty of Sports Science and Recreation, 2014)
This study examines the effects of organizational culture on organizational effectiveness in Islamic Azad Universities of Northwest of Iran. 75 academic members of physical education, voluntary filled out the Denison Organizational Culture (DOCS) and Hsu Organizational Effectiveness (OEQ). Statistical analysis of data (e.g. Pearson Correlation, Linear Regression and Multiple Regression) indicated that organizational culture has a significant positive influence on the organizational effectiveness. Only two indices of consistency and mission (organizational culture indices) have a significant positive influence on the organizational effectiveness. Also the results showed that organizational effectiveness has been affected 67.9% by organizational culture.